Voluntary Disclosure Practices and FII Flows - A Study of Selected Indian Firms - Rudra, Titas (Indian Journal of Finance, 2010)
Among many other factors like the legal system, institutional capacity, liquidity of capital market etc., information asymmetry has been identified as one of the important factors behind the home-biasness of investors worldwide- which can said to be removed by improved corporate disclosure. Previous literatures assessed the influence of accounting information on the international capital mobility. The study aims at contributing to the literature on the relationship between international capital mobility and financial reporting environment in the Indian context. In this study, the author establishes the firm-level relation between the voluntary corporate disclosure level and FII flows in India, if any, over the last decade. For the purpose of analysis, only voluntary disclosure quality has been considered as, to establish competitive advantage in the capital market; large and publicly traded leading Indian companies have gone beyond the minimum statutory disclosure requirements and compete with an extensive amount of business information voluntarily.